(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
The equation is used for a golden ratio family to calculate for a range of values of a in the modular ring Z4. The decimal part of ja is then used for x in the infinite series for which the associated sums are found. These lead to a series of generalized Fibonacci sequences.